Heat transfer performance, economic and environmental evaluations of a radiator cooling system employing CNT nanofluids - Tugba Tetik; Mustafa Armagan; Yasin Karagoz; Ercan Erturk (Ain Shams Engineering Journal, 2025)
This work presents an experimental study of a radiator cooling system using water-based nanofluids. Multi-wall carbon nanotubes (MWCNT) were dispersed in distilled water by 0.25, 0.5, and 0.6 wt%. According to the experimental results, employing MWCNT increases the total heat transfer by 30% in comparison with water. Also, using heat transfer results, the economic analysis of an internal combustion engine was performed. Lastly, the GWP (Global Warming Potential) results of engine was obtained. A novel improvement has been achieved by the use of MWCNT nanofluids.